Regioselective Synthesis of Indanones - van Leeuwen, Thomas; Neubauer, Thomas M.; Feringa, Ben L. (Synlett, 2014)
The degree of hydrolysis of polyphosphoric acid (PPA) has a crucial effect on the regioselectivity of the PPA-mediated synthesis of indanones. It was found that the regioselectivity can be switched by employing PPA with either a high or low content of P2O5. This methodology was used for the regioselective synthesis of a range of electron-rich indanones, including a natural sesquiterpene.
Keywords: indanones; polyphosphoric acid; electrophilic aromatic substitution; total synthesis; regioselectivity